2012
DOI: 10.1007/s10863-012-9419-2
|View full text |Cite
|
Sign up to set email alerts
|

3-bromopyruvate: Targets and outcomes

Abstract: The pyruvate mimetic 3-bromopyruvate (3-BP) is generally presented as an inhibitor of glycolysis and has shown remarkable efficacy in not only preventing tumor growth, but even eradicating existant tumors in animal studies. We here review reported molecular targets of 3-BP and suggest that the very range of possible targets, which pertain to the altered energy metabolism of tumor cells, contributes both to the efficacy and the tumor specificity of the drug. Its in vivo efficacy is suggested to be due to a comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
100
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(104 citation statements)
references
References 74 publications
(115 reference statements)
3
100
0
1
Order By: Relevance
“…3-BrPA has recently become a popular drug among research scholars worldwide (21). This drug is a glycolytic inhibitor that acts via hexokinase II and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and plays a critical role in apoptosis induced by intracellular ATP depletion.…”
Section: Discussionmentioning
confidence: 99%
“…3-BrPA has recently become a popular drug among research scholars worldwide (21). This drug is a glycolytic inhibitor that acts via hexokinase II and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and plays a critical role in apoptosis induced by intracellular ATP depletion.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that satellite cells are induced into activity following exposure of 3-BP a potent inhibitor of glycolysis [11]. However once they have emerged from their sub-basal position, we found that their migratory processes were attenuated.…”
Section: Discussionmentioning
confidence: 70%
“…We took advantage of the myostatin null mouse that contains much thinner ECM surrounding muscle fibers compared to that of a wild-type mouse. Secondly we exploited the availability of 3-Bromo pyruvate (3-BP) a small compound inhibitor that perturbs glycolysis [11]. Both studies reveal unexpected findings.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain more information on the mechanism of action of DIOS, enzyme inhibitors were applied: sodium fluoride (NaF) is a known inhibitor of enolase enzyme therefore it obstructs glycolysis, 3-bromopyruvic acid (3-BP) inhibits both hexokinase and pyruvate dehydrogenase enzymes [30,31], finally oligomycin A (OmA) inhibits the F O part of ATP synthase. Cells were treated with 10 lM DIOS in the absence and in the presence of different enzyme inhibitors for 12 h using the previously described conditions (Section 2.3.…”
Section: Investigation With Enzyme Inhibitorsmentioning
confidence: 99%